EVALUASI REFORMASI BIROKRASI DENGAN MENGGUNAKAN MODIFIKASI INDEKS PENGELOLAAN ASET - Yuhani, Octarina; Dyah Setyaningrum (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
The purpose of this study is to provide suggestions for improvements in the implementation of the Asset Management Index for measuring the performance of State Owned Assets as an intermediate indicator in the implementation of the Bureaucratic Reform evaluation. The method used in this research applies a qualitative research approach in the field of case studies with the object of research at the Directorate General of State Assets which is a work unit that has the authority to formulate State Property management policies. Data collection is done through document review and related literature as well as conducting semi-structured interviews. The results of this study illustrate the problems that still require significant improvement in the implementation of the Asset Management Index both from the aspects of processes, people, and tools so that the objectives of effective and efficient management of state property can be realized.